2016
DOI: 10.1128/genomea.00863-16
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Avian Escherichia coli Strain IHIT25637, an Extraintestinal Pathogenic E. coli Strain of ST131 Encoding Colistin Resistance Determinant MCR-1

Abstract: Sequence type 131 (ST131) is one of the predominant Escherichia coli lineages among extraintestinal pathogenic E. coli (ExPEC) that causes a variety of diseases in humans and animals and frequently shows multidrug resistance. Here, we report the first genome sequence of an ST131-ExPEC strain from poultry carrying the plasmid-encoded colistin resistance gene mcr-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 15 publications
1
14
0
1
Order By: Relevance
“…In China, some farmers use colistin to increase the quality of food animals, which they raise in their backyards. More importantly, the five reported mcr-1 –harboring STs identified in the current study (156, 10, 410, 88, and 131) had been previously isolated from poultry and swine (Bai et al, 2016 ; Ewers et al, 2016 ; Falgenhauer et al, 2016 ; Yang R. S. et al, 2016 ). This included ST10, the most prevalent ST in the current study, which has also been isolated from travelers returning from India (Bernasconi et al, 2016 ) and from European animals (El Garch et al, 2016 ).…”
Section: Discussionsupporting
confidence: 50%
“…In China, some farmers use colistin to increase the quality of food animals, which they raise in their backyards. More importantly, the five reported mcr-1 –harboring STs identified in the current study (156, 10, 410, 88, and 131) had been previously isolated from poultry and swine (Bai et al, 2016 ; Ewers et al, 2016 ; Falgenhauer et al, 2016 ; Yang R. S. et al, 2016 ). This included ST10, the most prevalent ST in the current study, which has also been isolated from travelers returning from India (Bernasconi et al, 2016 ) and from European animals (El Garch et al, 2016 ).…”
Section: Discussionsupporting
confidence: 50%
“…In conclusion, our report on the detection of mcr-1 in APEC associated with colibacillosis in production poultry is relatively new, and we could find only three other studies by Perreten and colleagues [61] and Yang et al [30] reporting mcr-1 in APEC in South Africa and China and a genome announcement of an avian ExPEC from Germany [31]. Regardless, our study would appear to be one of the first identifying mcr-1 in APEC from China and Egypt of earlier dates than previously reported.…”
Section: Discussionmentioning
confidence: 87%
“…The high abundance of ST 95 and ST 131 in this study is not unexpected. Both STs are commonly associated with disease and outbreaks in poultry where they may cause considerable economic loss and reduced animal welfare due to increased morbidity and mortality of the affected flocks [5,[25][26][27]. It may also be suggested that these STs have a zoonotic potential as they are also commonly found among human infections, the two STs are among the most common STs in bloodstream-and urinary tract infections [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%